The flexibility of gas - what is it worth? - Speirs,J; Jalil-Vega,F; Cooper,J; Gerber,Machado P; Giarola,S; Brandon,N; Hawkes,A (Sustainable Gas Institute, Imperial College London, 2020)
What is the evidence on the flexibility value that gas vectors and gas networks can provide to support the future energy system?There is an increasing debate regarding the use of gas networks in providing support for the decarbonisation of energy systems.The perceived value of gas “vectors” – encompassing natural gas, hydrogen and biomethane – is that they may provide flexibility, helping to support daily and seasonal variation in energy demand, and increasingly intermittent electricity supply as renewable electricity generation increases as a proportion of the electricity mix.Arguments in support of gas suggest that electricity systems will find it difficult to maintain flexibility on their own, whilst also reducing greenhouse gas emissions and increasing production to meet new demand for heating and transport. Gas, on the other hand, is expected to provide flexibility at relatively low cost, and may be produced and used with relatively low greenhouse gas emissions.White Paper 5 investigates the evidence surrounding the flexibility provided by gas and gas networks and the cost of, and value provided by gas to the future energy system.